Save the pulp is the essential issues on pulp capping treatment - Myrna N. Zakaria (DiscoverSys Inc., 2016)
Vitality of the pulp is a major key for the tooth to physiologically functioning in the mouth. Exposed pulp can be saved by pulp capping treatment diminishing the need for more complicated treatment such as root canal treatment or extraction. To induce tissue repair essentials factors must be considered namely proper case selection, method, material, adequate isolation and techniques. This literature review will discuss relevant issues and matters on pulp capping treatment based on evidence and findings from previous studies to achieve more predictable outcome of pulp capping treatment.